2006
DOI: 10.1111/j.1365-2265.2006.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mortality of severe hyponatraemia – a hospital‐based study

Abstract: Severe hyponatraemia in hospital patients is associated with prolonged admissions and significantly increased mortality compared with normonatraemic patients. A particular group at high risk of death are those whose Na levels fall after admission. They may represent a 'sicker' group, and deserve increased monitoring and surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
148
3
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(176 citation statements)
references
References 17 publications
8
148
3
17
Order By: Relevance
“…However, the significance of hyponatremia has been overlooked in clinical practice, and cases of mild chronic hyponatremia are generally considered benign (Decaux 2006). Recent studies have reported that hyponatremia is associated with a high mortality rate in various medical conditions (Baran and Hutchinson 1984;Tierney et al 1986;Gill et al 2006;Whelan et al 2009;Waikar et al 2009;Wald et al 2010). Hyponatremia is particularly prevalent in chronic liver disease and associated with a poor prognosis in patients with end stage liver disease waiting for a liver transplant (Angeli et al 2006;Kim et al 2008;Basto et al 2011).…”
mentioning
confidence: 99%
“…However, the significance of hyponatremia has been overlooked in clinical practice, and cases of mild chronic hyponatremia are generally considered benign (Decaux 2006). Recent studies have reported that hyponatremia is associated with a high mortality rate in various medical conditions (Baran and Hutchinson 1984;Tierney et al 1986;Gill et al 2006;Whelan et al 2009;Waikar et al 2009;Wald et al 2010). Hyponatremia is particularly prevalent in chronic liver disease and associated with a poor prognosis in patients with end stage liver disease waiting for a liver transplant (Angeli et al 2006;Kim et al 2008;Basto et al 2011).…”
mentioning
confidence: 99%
“…6 A variety of risk factors have been reported for hospital-acquired hyponatremia, including older age, diabetes mellitus, chronic kidney disease, surgery, pulmonary infection, diuretic therapy, administration of antibiotics, opioid analgesia, and the use of hypotonic intravenous fluids. [7][8][9] It is important to recognize that hyponatremia, while frequent, is not a trivial diagnosis. It is associated with serious complications that have been linked to increased morbidity and mortality.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is associated with serious complications that have been linked to increased morbidity and mortality. 1,8,[10][11][12][13] The presence of hyponatremia after an acute ST-elevation myocardial infarction in congestive heart failure and in patients with cirrhosis has been found to predict mortality. [10][11][12][13] Similarly, in critically ill patients, severe hyponatremia (serum [Na ? ]…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations